Twelve Months of Sundays : reflections on Bible readings, year B - Wright, N. T. (Nicholas Thomas) (London : SPCK, 2002)
"Drawn from his hugely popular columns in the British Church Times, and with new unpublished material, N.T. Wright's Twelve Months of Sundays weaves together scholarship, history, and fresh insights into the world and language of the Bible to add richness and a deeper understanding to the lectionary readings. Covering all the Sundays and major festivals for years A, B, and C in the lectionary cycle, this core resource by the renowned Anglican church leader, author, and scholar offers a brief commentary and reflection for each reading. Each section cites the lectionary references and offers a starting point for understanding the texts, drawing out points of connection between them. This book can be particularly useful in preparation for Sunday worship, for sermon preparation, or by anyhone whoe wants regular and straightforward Bible study throughout the year." - back cover.
Keywords: Bible -- Sermons; Church year sermons; Lectionary preaching